2020
DOI: 10.3390/ijerph17072213
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Paclitaxel–Carboplatin with Paclitaxel–Cisplatin as the Front-Line Chemotherapy for Patients with FIGO IIIC Serous-Type Tubo-Ovarian Cancer

Abstract: The use of weekly chemotherapy for the treatment of patients with advanced-stage serous-type epithelial Tubo-ovarian cancer (ETOC), and primary peritoneal serous carcinoma (PPSC) is acceptable as the front-line postoperative chemotherapy after primary cytoreductive surgery (PCS). The main component of dose-dense chemotherapy is weekly paclitaxel (80 mg/m2), but it would be interesting to know what is the difference between combination of triweekly cisplatin (20 mg/m2) or triweekly carboplatin (carboplatin area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 154 publications
1
16
0
Order By: Relevance
“…The administration of cisplatin to patients with hypersensitivity reaction to carboplatin was a concern owing to two deaths reported previously [ 20 , 21 ]. However, when combining the results of our study and previous reports [ 14 , 15 , 19 ], the incidence of hypersensitivity reaction to cisplatin was shown to be 31/183 (16.9%), with two deaths [ 16 , 17 ] (1.1%). While desensitization therapy is cumbersome and there are disadvantages in terms of temporal constraints, wTP is simple and easy to administer.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The administration of cisplatin to patients with hypersensitivity reaction to carboplatin was a concern owing to two deaths reported previously [ 20 , 21 ]. However, when combining the results of our study and previous reports [ 14 , 15 , 19 ], the incidence of hypersensitivity reaction to cisplatin was shown to be 31/183 (16.9%), with two deaths [ 16 , 17 ] (1.1%). While desensitization therapy is cumbersome and there are disadvantages in terms of temporal constraints, wTP is simple and easy to administer.…”
Section: Discussionsupporting
confidence: 76%
“…Since 2011, we have performed weekly administration of paclitaxel and cisplatin (wTP) in consecutive patients who developed carboplatin hypersensitivity reaction. Compared to dose-dense paclitaxel plus triweekly carboplatin, wTP with low-dose cisplatin has been reported to produce less hematologic toxicity, renal dysfunction, and anorexia, although the therapeutic effects of both regimens were similar [ 16 ]. The aim of this observational study was to investigate the safety and efficacy of wTP in patients with carboplatin hypersensitivity reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in recent 10 years, almost all of the randomized controlled trials and real-world studies on the progress of ovarian cancer chemotherapy have focused on targeted drugs.There are only a few studies on traditional chemotherapy drugs,and the scope of chemotherapy drugs is too narrow, all of them focus on paclitaxel,carboplatin and cisplatin.Gao [7]evaluated and compared the e cacy of post-operative chemotherapy using paclitaxel plus carboplatin or nedaplatin in patients with ovarian cancer,as well as the effects of different combinational therapies on the survival times of patients,The results showed that chemotherapy had a signi cant effect on the survival time of patients,and carboplatin plus paclitaxel should be the rst choice for the initial treatment of ovarian cancer.A recent randomized controlled trial [17]compared the effects of weekly paclitaxel (80 mg/m 2 ) combined with three weeks of cisplatin (20 mg/m 2 ) or three weeks of carboplatin (AUC 5-7) chemotherapy on the prognosis of epithelial ovarian cancer after primary cytoreductive surgery,The results showed that the median PFS and median OS of paclitaxel carboplatin group were better than those of paclitaxel cisplatin group, but the difference was not statistically signi cant,the incidence of adverse events (such as myelosuppression) of paclitaxel carboplatin group was higher, and the prognosis of patients with chemotherapy cycle > 21 weeks was worse than that of patients with chemotherapy cycle≤21 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Some molecular signaling mechanisms like a chronic inflammatory response, oxidative stress (OS), apoptosis, and angiogenesis are associated with the development of OVC [3]. Chemotherapy is the first-line treatment for OVC, co-administration of carboplatin and paclitaxel is mostly applied [18] but recurrence and eventual resistance are common [19]. Recently developed chemotherapies that act as the PARP inhibitors, checkpoint inhibitors, anti-angiogenic agents are blended with conventional chemotherapeutic agents for clinical trials [20].…”
Section: Introductionmentioning
confidence: 99%